The Kinetics of Small Extracellular Vesicle Delivery Impacts Tissue Regeneration - Antunes, Helena (2019)
FCT (SFRH/BDE/103512/2014;SFRH/BPD/112883/2015; SFRH/BPD/97286/2013; MITP-TB/ECE/0013/2013; EXCL/DTP-PIC/0069/2012; UID/NEU/04539/2013); EFSD/JDRF/Novo Nordisk European Programme in Type 1 Diabetes Research; QREN-COMPETE funding (FCOMP-01-0202-FEDER-038631; Project “ExoCord” promoted by Stemlab, SA and Biocant), Portugal 2020-COMPETE funding (Project “Stem cell based platforms for Regenerative and Therapeutic Medicine”, Centro-07-ST24-FEDER-002008; Project “StrokeTherapy” co-promoted by Stemlab, Rovisco Pais and Universidade de Coimbra, POCI-01-0247-FEDER-003386) and EC project ERAatUC (Ref:669088).